The Effect of Product Innovation on Customer Loyalty: A Study on a Beverage Brand - Dian Putri Amanda; Eka Yuliana (International Journal of Economics, Business and Innovation Research, 2024)
This study aimed to determine Menantea's product innovation according to customers in DKI Jakarta and West Java and to measure customer loyalty in the region. In addition, this study also aims to determine how product innovation affects customer loyalty. The research employs a quantitative approach, with a sample size of 100 respondents. The population for this study consists of Menantea customers located in DKI Jakarta and West Java. The approach used is sampling by probability sampling with the simple random sampling method. Simple linear regression analysis and descriptive analysis were used to process the data. The findings of the descriptive analysis indicate that Menantea's product innovation is well-received, and customers in DKI Jakarta and West Java have a high level of loyalty. The simple linear regression analysis findings indicate that the Product Innovation variable positively affects the Customer Loyalty variable. Based on the study results, the company is expected to focus on developing and diversifying product variants by considering customer feedback and market trends and launching new unique variants to increase consumer preference.